INOVASI PEMBELAJARAN PPKN: EFEKTIVITAS MEDIA FLIPBOOK BERBASIS HEYZINE UNTUK MATERI BHINNEKA TUNGGAL IKA KELAS IV SD - Gde Oka Samahita; L. Heny Nirmayani; Putu Eka Sastrika Ayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to evaluate the effectiveness of using Heyzine-based digital flipbook media in enhancing students' cognitive understanding and affective engagement regarding